PEMBERDAYAAN BUDAYA LITERASI MENULIS PUISI PADA PESERTA DIDIK DALAM MENGHADAPI ERA REVOLUSI INDUSTRI KREATIF - Yani, Sari; Susanti, Novi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The term literacy began to become a lot of discourse in the mass media and the world of education after Anies Baswedan, compilation into the Minister of Education and Culture, launched the School Literacy Movement (GLS). Currently following global change, the Indonesian revolutionary era is also developing a creative industry, an era of revolution that is in dire need of creative industry products. The creative industry can be defined as an industry based on expertise, talent and creativity; such as fashion, crafts, published (books and print media), music, film, and advertising. Literature, literary works and creative industries, both based on talent and creativity and together with cultural nuances. The difference is that the process of publishing literary works is more oriented to literary interests, while creative industries are more oriented to market interests. Language literacy becomes very important in the era of creative industries, so there are products based on creative industries that are language-based. This paper begins to reveal steps that can be taken so that literacy culture or GLS can continue to run in accordance with the development of the existing creative industry. The method used is of course descriptive and through qualitative consultation. In conclusion, the Indonesian literacy movement still needs to be encouraged, and Indonesian language learning in schools and colleges is still necessary, so that people become more proficient in supporting Indonesia and still love Indonesian as a communication tool, cultural imagery, and national identity reinforcement. The low ability of students in the art of poetry proves the need for empowerment to write poetry for students. This article discusses how to empower the literary writing culture of students in the struggle of the creative industrial revolution.